Blade Runner : betwen past and future - Menezes, Paulo (Tempo Social, 1999)
Blade Runner is not only a film about the future. The Ridley Scott's version, remaked in 1993, show us dimensions that the first one had dissolved. Relations concerning past, present and future are the emphasis now, in order to question the linear conception of time and the relations between men and his own time and history. The temporality of the so called specific human kind emerges from the search towards his own memory which can prove his existence as human being and thus as master of his past and live.